Etiological factors for mandibular fractures in transoperative period of tooth extraction: systematic review (Research, Society and Development, 2020)
Objectives: to analyze the possible etiological factors associated with mandibular fractures occurring during tooth extractions. Methods the following data were collected: sex, age, the extracted tooth, tooth classification, angulation, level of bone impaction, pathological association, recognized technical errors, instruments used at the time of the fracture, and the surgeon’s experience and specialization, if applicable. An electronic search of the following databases was performed: PubMed/Medline, Lilacs, Embase, and Scopus. The data were tabulated and analyzed using the Chi-square test, a P-value less than 0.05 was considered significant. Results: a total of 80 cases were selected. Sex and age were not statistically significant (P>0.05). The teeth most associated with fractures were the mandibular third molars; however, the location was not significant. Pell & Gregory classes II, B, C, mesio-angular teeth, partial bone impaction, teeth related to pathological process, application of excessive strength, extractions with elevators, and non-specialists showed greater association with mandibular fractures during transoperative time (P